Aggressive behavior and its relationship to social awareness among middle school students (Journal of the College of Basic Education, 2022)
The aims of research to identify currentaggressive behavior among middle school students2-social awareness among students of middle school3-relationship between aggressive behavior and social awareness among students of middle school4-The difference in the relationship between aggressive behavior and social awareness among middle school students, according to gender (male female). You may accept theories that the researchers interpreted the concepts of search and follow the proper procedures for the purpose of applying Adata search has been using statistical methods, namely:1-Pearson correlation to extract stability coefficient as well as the relationship between the variables of research.2-t. test of one sample to extract denote the difference between the center and the central premise sample.3-t. test for two independent samples to extract the discriminatory power and present research has concluded the following results this result we have given the impression that the greater social awareness least aggressive behavior as the link was positive proportional, and the results showed that there are differences in the relationship between aggressive behavior and social awareness among students of middle school, according to gender (male female) have researchers took a series of recommendations and proposals